Burden of colon and rectum cancer attributable to processed meat consumption in China, 1990–2021 - Zhan, Zhouwei; Chen, Xiamei; Zheng, Jinping; Xu, Jingjie; Zhou, Sijing; Guo, Zengqing; Chen, Bijuan (Frontiers in Nutrition, 2025)
BackgroundColon and rectum cancer (CRC) poses a significant public health challenge, and diets high in processed meat have been identified as key risk factors. This study aims to assess the burden of CRC attributable to processed meat consumption in China from 1990 to 2021, focusing on mortality, disability-adjusted life years (DALYs), years lived with disability (YLDs), and years of life lost (YLLs).MethodsData were obtained from the Global Burden of Disease (GBD) study for CRC attributable to processed meat consumption in China from 1990 to 2021. The analysis included age-standardized rates for deaths, DALYs, YLDs, and YLLs, alongside age-period-cohort (APC) and decomposition analyses to examine temporal trends and contributing factors. Joinpoint regression was used to detect significant changes in trends.ResultsThe burden of CRC attributable to processed meat consumption in China increased significantly between 1990 and 2021. In 2021, males exhibited higher mortality and DALY rates than females, particularly in older age groups. The age-standardized death rate rose from 0.23 to 0.32 per 100,000, and DALYs increased from 5.83 to 8.57 per 100,000. Joinpoint analysis revealed steep rises in DALYs and YLLs, especially during 2007–2011. APC analysis showed that older cohorts consistently exhibited higher death rates, while more recent cohorts displayed lower mortality. Decomposition analysis indicated that population growth and epidemiological changes drove the rise in mortality, with aging contributing to a reduction in deaths. These factors had a more pronounced impact on males.ConclusionThe study highlights the growing burden of CRC linked to processed meat consumption in China over three decades, with significant gender differences and strong cohort effects. The findings call for targeted interventions to reduce processed meat consumption and mitigate CRC risk.